Thermal behavior of polymeric nickel(II) oxalate complex obtained through nickel(II) nitrate/ethylene glycol reaction - Niculescu Mircea; Pascariu Mihai-Cosmin; Racu Andrei; Taranu Bogdan-Ovidiu (Journal of the Serbian Chemical Society)
This paper describes the analysis of the thermal decomposition of polymeric nickel (II) oxalate complex, a homopolynuclear coordination compound having the formula [Ni(C2O4)(H2O)2]n⋅xnH2O. The thermolysis was conducted in both dynamic oxidative and inert atmospheres by simultaneously applying thermogravimetry (TG), differential thermogravimetry (DTG) and differential thermal analysis (DTA). The proposed decomposition mechanism was confirmed using evolved gas analysis (EGA) technique via the Fourier transform infrared spectroscopy (FTIR) of the gaseous decomposition products. The solid- -state decomposition products formed during heating were investigated by chemical analysis, FTIR, Raman spectroscopy and X-ray diffraction (XRD). The structure, morphology and properties of the final decomposition products were characterized by XRD, FTIR, energy dispersive X-ray spectroscopy (EDX) and transmission electron microscopy (TEM). These analyses show that the final decomposition product in oxidative atmosphere was nickel oxide, shaped as polygonal particles with widely distributed sizes. As for the results in inert atmosphere, they outlined a mixture of Ni and NiO as rhombohedral particles in a 3:2 mole ratio.